(untitled) - Gleitman, Henry (New York, 1995)
In an era marked by specialisation and fragmentation, Gleitman's "Psychology" has always recognised that drawing connections to other disciplines, particularly the liberal arts and sciences, as well as to the field's historical dimensions, helps show students how and why psychology is relevant to the world around them. The seventh edition of "Psychology" continues this project, introducing a unified approach built around a new part structure, thought provoking questions and contemporary themes, providing students with the most coherent picture of the field.
Keywords: Psychology,Tâm lý học; Textbooks,Sách giáo khoa